The Principal's Initiatives to Enhance Teachers' Instructional Skills - Sa'imah, Sa'imah; Fitria, Happy; Kristiawan, Muhammad (Graduate Program Magister Manajemen Pendidikan, 2023)
The skill of teachers to teach in schools will determine the quality national education. The purpose of this study is to describe school principals’ efforts to improve teachers’ teaching skills. Data collection methods were documentation, interviews, observation, and a review of the literature. Descriptive qualitative analysis techniques were used in data analysis. The results obtained indicate that school principals’ efforts to improve teachers’ teaching skills through planning, implementing, and evaluating teacher competency improvement programs were technically successful and had a positive impact on teachers’ teaching performance. The establishment of a strategic program to improve teacher’s teaching skills, which refers to the school’s vision of producing students with high morals, intelligence, and discipline, has an impact on the quality of the teaching and learning process at SMA Negeri 2 Kayuagung.